Strategi Pengembangan Usaha UMKM dengan Analisis SWOT - Rusman Maulana (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to evaluate business development strategies by applying the SWOT analysis method (Strengths, Weaknesses, Opportunities, Threats) as a tool in the strategic planning process. The method used is a literature review, in which data were obtained by examining various academic sources such as books, journals, and relevant research reports. The findings of this review indicate that SWOT analysis provides a comprehensive understanding of a business's internal and external conditions. By leveraging strengths and opportunities while identifying weaknesses and threats, business actors—especially MSMEs—can design more focused and realistic strategies, such as SO, WO, ST, and WT strategies. SWOT analysis is not only theoretical but has also proven effective in various business development contexts. Therefore, the application of this method is highly recommended as a foundation for formulating sustainable business development policies and directions.